2009
DOI: 10.1002/ejoc.200801169
|View full text |Cite
|
Sign up to set email alerts
|

Click Multivalent Heterogeneous Neoglycoconjugates – Modular Synthesis and Evaluation of Their Binding Affinities

Abstract: The efficient synthesis of structurally diverse, multivalent, heterogeneous neoglycoconjugates by means of a series of different click‐based strategies is described. The methodology is highly efficient and versatile allowing for easy access to a series of mannose (α‐Man)‐containing glycoconjugates differing in their valency, nature of the scaffold, nature of the constitutive sugars and length of the linker. The influence of those structural parameters on the binding affinities of these glycomimics toward Conca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 89 publications
3
37
0
Order By: Relevance
“…The Dowex M-4195 resin was purchased from Supelco and subjected to a conditioning treatment. The vinyl sulfone propyl silica gel 5, [28] the aminopropyl silica gel 6, [29] the alkynes 10, [38] 15, [39] 16, [40] 17, [41] 18 [42] and 19, [43] the azides 21, [44] 22, [45] 23, [46] 24, [47] 25, [48] 27, [49] and 28 [50] and the alkyne and azido functionalized silicas [33] used as click scavengers were prepared according to reported procedures in literature. TLCs were performed on Merck Silica Gel 60 F 254 aluminium sheets.…”
Section: Experimental Section Generalmentioning
confidence: 99%
“…The Dowex M-4195 resin was purchased from Supelco and subjected to a conditioning treatment. The vinyl sulfone propyl silica gel 5, [28] the aminopropyl silica gel 6, [29] the alkynes 10, [38] 15, [39] 16, [40] 17, [41] 18 [42] and 19, [43] the azides 21, [44] 22, [45] 23, [46] 24, [47] 25, [48] 27, [49] and 28 [50] and the alkyne and azido functionalized silicas [33] used as click scavengers were prepared according to reported procedures in literature. TLCs were performed on Merck Silica Gel 60 F 254 aluminium sheets.…”
Section: Experimental Section Generalmentioning
confidence: 99%
“…A few other studies have also reported that lectin binding to glycan mixtures is stronger than the binding to a single glycan. [811] However, the mechanism of such hetero-multivalency is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies suggested that the combination of different binding or non-binding sugars and their simultaneous multivalent presentation on a single scaffold can influence the resulting binding properties in both affinity and selectivity e.g. towards a specific protein receptor (49,50). Thus it would be highly relevant to obtain and study sequence-defined heteromultivalent glycomacromolecules presenting different sugar ligands at defined positions along the scaffold.…”
Section: Monodisperse Sequence-defined Glycomacromolecules Via Solidmentioning
confidence: 99%